Erotic Education: Elaborating a Feminist and Faith-Based Pedagogy for Experiential Learning in Religious Studies - Carbine, Rosemary P. (Teaching theology and religion, 2010)
This essay explores intersections among Jesuit, Quaker, and feminist theologies and pedagogies of social justice education in order to propose and elaborate an innovative theoretical and theological framework for experiential learning in religious studies that prioritizes relationality, called erotic education. This essay then applies the relational rationale of erotic education to interpret the author's design of a service or community-based learning component in a course about contemporary U.S. Christian social justice movements, offered in both religiously-affiliated and religiously-inspired liberal arts colleges. The course case study not only chronicles the author's evolving pedagogical praxis as a feminist theologian teaching in Jesuit and Quaker institutions, but also is grounded in how the author's course embodies erotic education, that is, how specific objectives, learning practices, and assignments build and bolster relationships among students (in peer-to-peer small groups inside and outside the classroom) as well as among students and their community sites. In developing this framework and implementing it within this particular course, the author argues that erotic education emphasizes the naming and training of our existential desires for interpersonal relations in order to upbuild not only the individual but also the common good.